NANOPARTÍCULAS DE PRATA (AGNPS) ALTERAM A EXPRESSÃO GÊNICA HIPOTALÂMICA HIPOFISÁRIA E GONADAL - WILK, REBECA (2017)
Silver nanoparticles AgNPs have been widely used as components of various commercial products both medical and industrial because of their bactericidal properties. Despite its wide range of use, its toxicological effects are still not well understood. They may present cytotoxicity, genotoxicity, blockage in mitochondrial activity, influence on development and weight, germ cell toxicity, and delay the age at puberty. The prepubertal period is a very sensitive period, where the hypothalamic pituitary testicular axis (HPT) undergoes morphophysiological changes, which may alter the hormonal levels and the onset of puberty. AgNPs are able to function as potential endocrine disrupting chemical, affecting spermatogenesis, but few studies report the effects on the hypothalamic-pituitary-gonadal axis. The objective was to verify the AgNP toxicity in rats through evaluation of body development, age at puberty, weight of the reproductive organs, and expression of genes related to HPT function and hormonal profile. Sixty rats were used in 5 groups treated with the doses: 0, 15, 7.5, 3.75 or 1.875 μg/kg. Puberty delay, increase in Gnrh mRNA expression, decreased Esr1 and Esr2 mRNA were observed. In addition, a decrease in mRNA in both Ar and Esr2 was observed, with an increase in Inhbb mRNA and in serum LH and FSH levels in the 3.75 and 1.875 groups respectively. It was concluded that the prebubertal AgNP exposure alters the gene expression in the HPT axis and alters the age at puberty and the hormonal serum levels.